Public Acceptance And Resistance Regarding The Government Policy About Prohibiton Of Mudik Eid Al-Fitr 2021 Amid The Covid-19 Pandemic - Balqis Ghaida, Diajeng; Prihantoro , Edi (International Journal of Educational Research & Social Sciences, 2024)
The prohibition of Mudik Eid Al-Fitr in 2021 is a policy that aims to reduce the spread of Covid-19. However, Eid is also a hereditary tradition of the Indonesian people, the majority of whom are Muslims. As a result of this policy, many informants accepted and resistance the policy with their respective attitudes according to their situation and conditions. The purpose of this study is to find out how the attitude of acceptance and resistance is related to government policies. This study uses a qualitative approach with depth interviews also observation methods and uses a constructivism paradigm. In this research, using an Information Integration Theory, Resistance Theory and Loss Theory by using 5 phases consisting of rejection phase, anger phase, bargaining phase, depression phase and acceptance phase. There are 5 informants who accepted the policy and 5 informants who resistenced the policy. The results of this study indicate that 5 informants accepted the policy due to self-awareness and advice from families who forbade returning to their hometown. Meanwhile, 5 informants who resistanced the policy were caused by policies that made informants confused, personal matters and the desire to celebrate Eid with family in their hometown.